DESENVOLVIMENTO DE UMA METODOLOGIA ELETROANALÍTICA PARA A DETERMINAÇÃO DE CAFEÍNA EM COGUMELOS CULTIVADOS COM RESÍDUOS DE CAFÉ - Kultz, Thiellen Wrobel (2017)
The mushrooms are living organisms belonging to the Kingdom Fungi, and have several purposes in cooking, ornamentation, in medicine, as well as hallucinogenic and poisonous purposes too. There has been an increase in the interest in the production and consumption of edible mushrooms, such as the mushroom Pleurotus. The cultivation of this mushroom is performed using various extracts such as sugar cane, wheat bran and waste as seeds and coffee grounds. The chemical composition of the mushrooms is influenced by the substrate on which it is grown, where absorption may occur from compounds originally present in the same. This study had as its focus the mushroom Pleurotus and as main objective the determination of caffeine in edible mushrooms of the genus Pleurotus who had presence of residues of coffee, at least in a part of its cultivation. The present work presents the study of optimization of parameters of eletroanalíticas techniques of square wave voltammetry (VOQ) and cyclic voltammetry as well as validates. To confirm the validation of the method for determining eletroanalítico were evaluated the parameters, linearity, limits of quantification and detection, precision and accuracy, which were obtained by using different statistical techniques. The results indicated that the method used presents good accuracy, due to low recovery rates with averages of approximately 107.9%. The method is precise when evaluated in terms of repeatability and intermediate precision, with values of 9,79 and 10,02 percent respectively. The limits of detection (LOD) and quantification (LQ) of 0.98 μmol/L and 0.29, respectively, were low, demonstrating the sensitivity of the square wave voltammetry technique. There is also the good linearity in the range of concentrations of 0.91 to μmol/L 10.3, with values of Fregressão (3563.26) > Fcrítico (4.68), without evidence of lack of adjustment to the linear model (Ffaj (0.85) < Fcrítico (2.65), p > 0.05). Through the validated method, it has been found that the mushroom that presented in steps of cultivation and coffee residues introduced inoculum concentrations of caffeine approximately 1.20 mg/g and the mushroom which had its inoculum in ryegrass and straw cultivation on coffee seed showed concentrations of 0.7 mg/g, so both samples showed significant levels of caffeine, thus demonstrating that the mushroom is able to absorb caffeine from the substrate.